ANALISIS ESTIMASI LAJU EROSI DI DAS MALUKA PROVINSI KALIMANTAN SELATAN DENGAN MODEL E30 - Ilmi, Zainal; Badaruddin, Badaruddin; Suyanto, Suyanto; Fithria, Abdi (Universitas Lambung Mangkurat, 2023)
Problems in the Maluka watershed such as flood disasters are an indication that the management of the Maluka watershed still needs continuous and targeted improvement, one indication of the cause of the flood problem is the high rate of erosion in the Maluka watershed, several studies have been conducted in parts of the Maluka watershed area, but comprehensive erosion rate data in the Maluka watershed area still does not exist so that this Erosion Rate Estimation research with the E30 Model can be an answer and will produce data in the form of Geospatial data that can be a reference for watershed management information systems, The research method uses the E30 Model which only requires three parameters, namely NDVI data obtained from Sentinel 2-MSI Imagery, slope data obtained from DEM data and sample data of the miminum erosion rate and maximum erosion rate in the Maluka watershed at a slope of 30 degrees taken during one year, from field sample data shows a minimum erosion rate of 29.23 mm/year and a maximum erosion rate of 83.67 mm/year, analysis of erosion rate estimation with the E30 model in the Maluka watershed shows the highest erosion rate in the Maluka watershed 1. 000- 1,299.72 tonnes/ha/year covering 128 hectare, 0.15% of the Maluka watershed area. The smallest erosion rate in the Maluka watershed is 0-15 tonnes/ha/year covering 8,180 hectare, 9% of the Maluka watershed area. Very severe Erosion Hazard Level (IV-SB) is located in the upper area of the Maluka watershed which is dominated by steep slopes, especially in the Banyu irang sub-watershed which does have a higher slope level than the Bati-bati sub-watershed. The erosion rate of 180-480, which indicates Severe Erosion Hazard Level (III-B), is spread over more gentle areas, while Moderate Erosion Hazard Level (III-S) dominates in the middle and lower reaches of the Maluka watershed.